The Role of Fishermen Wives in Improving Family Economy in Karangsari, Tuban Sub-District, Tuban Regency - Purwanto, Hendra; Rusdarti, Rusdarti; Prasetyo, P. Eko (Universitas Negeri Semarang, 2020)
Small number of fisherman’s catch in certain seasons due to bad weather and the life of fishermen that is generally poor, resulting in the fishermen's wife to work in order to help her husband to make ends meet. The purpose of this study is to determine: the economic condition of fishermen's families in terms of the characteristics of fishermen's wives, the multiple roles of fishermen's wives, and the impacts arising from the multiple role in improving the family's economy, as well as the contribution of fishermen's wives in the family economy in Karangsari, Tuban sub-district. This research uses survey methods. Respondents were taken by purposive sampling. Data analysis is performed descriptive qualitatively. While the data collection contains the identification of fishermen's wife respondents who have a multiple roles to help the fishermen's family economy, meanwhile the questionnaire contains the characteristics of fishermen's wives, the activities of fishermen's wives, the impact of the fishermen's wife's multiple roles, and the contribution of fishermen's wife's income. The results of this research is that the multiple role of fishermen's wives in the domestic realm as housewives who take care of household activities such as cooking, washing, cleaning the house, taking care of their husbands and children, they also take the time to help their husbands (public domain) work as fresh fish sellers, manage and sell smoked fish, manage and sell salted fish, and open a food stall or grocery store. While the positive impact of the wife’s multiple roles is the increasing family income, increasing the economic and social status of the family and making ends meet, while the negative impact is the reduced time to gather with the family, changes in the capacity of homework, and quarreling husband and wife which are no more than 1 or 2 days. While the income earned by the fishermen's wife contributes quite significantly in helping to overcome the expenditure of daily needs of the fishermen's household.